Self-Administered Procedural Analgesia Using Nitrous Oxide/Oxygen (50:50) in the Pediatric Surgery Emergency Room: Effectiveness and Limitations - Heinrich, Martina; Menzel, Claudia; Hoffmann, Florian; Berger, Michael; Schweinitz, Dietrich von (European Journal of Pediatric Surgery, 2015)
Introduction Minor surgical interventions in children are often at times challenging due to the lack of cooperation by the child. Procedural sedation and analgesia is often appropriate, but unpleasant or painful applications of medication add additional discomfort to the child. A mixture of nitrous oxide (N2O)/oxygen (O2) in a ratio of 50:50, functioning as an inhalational sedative analgesic, may be a viable alternative, in particular in an emergency care setting because such mixtures require no fasting period and are self-administered. Therefore, in this study we investigated the feasibility and the effectiveness of N2O/O2 (50:50) as a sedative analgesic when performing minor surgical procedures.Patients and Methods Procedural sedation and analgesia with an N2O/O2 (50:50) mixture applied during minor surgical procedures were prospectively evaluated over 2.5 years in a major pediatric hospital in Germany. Indications for sedation were either minor painful interventions, the injection of a local anesthetic, or a digital block in an emergency care setting. Diagnosis, type of surgery, inhalation time, complications, side effects, pain scores, and the child's behavioral reaction were assessed.Results A N2O/O2 (50:50) mixture was administered in 210 children, ages 2.7 to 16.5 years (mean 9.0 years). Three treatments were terminated because of lack of compliance, nausea, or dizziness. No other side effects were encountered. During the intervention, 80.5% of all patients were pain free, and 81.9% were relaxed and calm. A higher rate of insufficient pain control was observed when the indication was an injection of a digital block or a reposition of fractures and dislocations.Conclusions The use of self-administered N2O/O2 (50:50) mixture for minor painful procedures in children is safe and adequate pain control can be achieved in most cases. The benefits of this approach for the child and its parents are its good acceptance and adequate pain control. The benefit for the health care provider is the lack of a fasting period before administration, good anxiolysis at minimum sedation, and a cooperative patient. Limitations are unsatisfying analgesia in some cases. Though not found in our study, potentially serious adverse events are a possibility and standard safety guidelines for minimal sedation should always be applied.
Keywords: nitrous oxide; children; inhalation route; pain; minor surgery